2021
DOI: 10.14309/ctg.0000000000000372
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Trends in Hospitalizations for Comorbid Chronic Liver Disease and Substance Use Disorders

Abstract: INTRODUCTION: Chronic liver diseases (CLDs) and substance use disorders (SUDs) are increasingly prevalent and often coexist. Contemporary studies describing the characteristics and hospitalization trends of those with comorbid CLD-SUD are lacking. We aimed to characterize a population-based cohort with comorbid CLD-SUD and describe trends in these hospitalizations over time by individual-level characteristics. METHODS: We performed a cross-sectional analysis of the Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“… 36 , 37 In regards to substance use, our study identified a recent rising incidence of AUD and SUD, which also mirrors national trends. 38 , 39 A recent cross-sectional analysis by Desai et al 40 evaluating US hospitalization trends found a rise in comorbid CLD-SUD hospitalizations resulting in higher rates of inpatient mortality than CLD alone, and during the COVID-19 pandemic there has been a rise in alcohol-associated hepatitis waitlistings and liver transplantation. 41 While we observed a parallel increase in the number of general mental health clinic visits per year in line with the rising incidence proportion of broad mental health diagnoses, there was a gradual decline in overall AUD/SUD-related visits despite a recent rising incidence proportion of AUD/SUD.…”
Section: Discussionmentioning
confidence: 99%
“… 36 , 37 In regards to substance use, our study identified a recent rising incidence of AUD and SUD, which also mirrors national trends. 38 , 39 A recent cross-sectional analysis by Desai et al 40 evaluating US hospitalization trends found a rise in comorbid CLD-SUD hospitalizations resulting in higher rates of inpatient mortality than CLD alone, and during the COVID-19 pandemic there has been a rise in alcohol-associated hepatitis waitlistings and liver transplantation. 41 While we observed a parallel increase in the number of general mental health clinic visits per year in line with the rising incidence proportion of broad mental health diagnoses, there was a gradual decline in overall AUD/SUD-related visits despite a recent rising incidence proportion of AUD/SUD.…”
Section: Discussionmentioning
confidence: 99%
“…Data were obtained from the Healthcare Cost and Utilization Project (HCUP) National Inpatient Sample database (NIS) between 2009 and 2018. The HCUP NIS has been extensively described elsewhere . This study is reported following the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) reporting guideline.…”
Section: Methodsmentioning
confidence: 99%
“…All hospital discharges for individuals aged 18 years and older from 2009 to 2018 were assessed for inclusion. Admissions were included if they contained at least 1 cirrhosis-related International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) and International Statistical Classification of Diseases, Tenth Revision, Clinical Modification (ICD-10-CM) codes and at least 1 cirrhosis-related complication ICD-9-CM or ICD-10-CM code (ie, ascites, HE, VH, and hepatorenal syndrome [HRS]) . eFigure 1 in Supplement 1 provides the flowchart of study participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, a recent national inpatient database analysis reports a disproportionate increase in hospitalizations for nonalcoholic fatty liver disease for those with comorbid CLD and SUD (74% in CLD alone vs. 320% in CLD and SUD) 19 . This highlights the evolving need for integrated and tailored care, with increasing SUD, obesity, and nonalcoholic fatty liver disease.…”
Section: Integrated Cld‐sud Treatmentmentioning
confidence: 99%